Application of Computer Graphics to Performance Studies of Missile Warheads - Rao, K. Rama; Murthy, K.P.S.; Patkar, M.R. (Defence Science Journal, 2013)
Intercept geometry of target aircraft and missiles play an important role in determining the effectiveness of the warhead. Factors such as fragment spatial distribution profile, damage capabilities, target and missile characteristics have been considered and visualised through computer graphics and optimum intercept intercept angles have been arrived. Computer graphics has proved to be an important tool to enhance perception and conceptual design capabilities in the design environment.